The Interpersonal Meaning of Javanese Catholic Daily Prayers - Ratna, Kusumawardhani (Universitas PGRI Semarang, 2010)
Abstract Prayer is created in a certain cultural and situational context. Prayer also contains interpersonal meaning. The purpose of the study is aimed at describing the realization of interpersonal meaning found in Javanese Catholic daily prayers. The study is a descriptive qualitative research as the aim of the study is to describe the interpersonal meaning of Javanese Catholic daily prayers. The study was conducted based on clause, modality, and appraisal devices . Clause analyses and its modality are used to know the relation between the speaker and the addressee. Here, the relation between Catholic people and God, Hail Mary, or Jesus Christ. While the appraisal devices are used to know the way Catholic people express the prayers. They are attitude, amplification, source, and speech level. The result is shown in 1) speech functions; speech roles, and 3) the appraisal of Javanese Catholic Daily prayers. As the texts are prayers, the speech functions found in English prayers are giving information and demanding goods and services. The speech roles of?Ã©?Ã¡ Javanese prayers are statements and demands. It is suggested that prayers are good media for teaching languages. By knowing the interpersonal meaning of the prayers, people are able to say the prayers correctly. They will express their statements and demands politely as the addressee is God. Key words: interpersonal meaning, Catholic Prayers, speech function, speech roles, appraisal system